IMPLEMENTASI KEBIJAKAN GERAKAN MASYARAKAT MAGRIB MENGAJI - Febri Yuliani, Elita, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2020)
Implementing the Policy of the Islamic Maghreb Community Movement. This study aims to determine the implementation of the Magrib Mengaji community movement policy in Tapung Hilir District. This type of research is a descriptive qualitative approach. The research informants consisted of Officials and Staff of the Ministry of Religion in Kampar District, Ulama and Community Stores. Data collected through interviews, observation and documentation. The results of this study indicate that the implementation of the Koran community movement policy in the Tapung Hilir sub-district is not well implemented because there are still obstacles that hamper the implementation of the policy, and the impact of the existence of the study sunset recitation policy in the Tapung Hilir sub-district has not significantly positive impact.